1971
DOI: 10.1037/h0031015
|View full text |Cite
|
Sign up to set email alerts
|

Selective responding by autistic children to multiple sensory input.

Abstract: Three groups of children (autistic, retarded, and normal) were reinforced for responding to a complex stimulus involving the simultaneous presentation of auditory, visual, and tactile cues. Once this discrimination was established, elements of the complex were presented separately to assess which aspects of the complex stimulus had acquired control over the child's behavior. We found that: («) the autistics responded primarily to only one of the cues; the normals responded uniformly to all three cues; and the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
188
0
19

Year Published

1981
1981
2016
2016

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 432 publications
(218 citation statements)
references
References 20 publications
4
188
0
19
Order By: Relevance
“…Concordantly, Hermelin and O'Connor (1970) found that children with autism displayed different behavioural and physiological responses to visual and auditory stimuli than did matched TD and learning-disabled children. These and other related findings (e.g., Hermelin & O'Connor, 1971;Lovaas, Schreibman, & Koegel, 1971) suggested that individuals with autism relied on different aspects of the stimulus sensory cue or channel than TD children and that the repetitive motor movements of children with autism provided kinesthetic feedback to better cope with sensations in their environment including a sense of their body in space (Ornitz, 1974). These studies were plagued with poorly defined constructs and samples and unsophisticated methodology, thus, the findings lacked validity and reliability.…”
Section: Early Behavioural Studiesmentioning
confidence: 95%
“…Concordantly, Hermelin and O'Connor (1970) found that children with autism displayed different behavioural and physiological responses to visual and auditory stimuli than did matched TD and learning-disabled children. These and other related findings (e.g., Hermelin & O'Connor, 1971;Lovaas, Schreibman, & Koegel, 1971) suggested that individuals with autism relied on different aspects of the stimulus sensory cue or channel than TD children and that the repetitive motor movements of children with autism provided kinesthetic feedback to better cope with sensations in their environment including a sense of their body in space (Ornitz, 1974). These studies were plagued with poorly defined constructs and samples and unsophisticated methodology, thus, the findings lacked validity and reliability.…”
Section: Early Behavioural Studiesmentioning
confidence: 95%
“…This theory posits that over-selective responding is caused by an inability to attend to all component elements of a stimulus. Stimuli that are not attended to cannot be processed or learned about; therefore, only the elements of the stimulus that are attended to can subsequently control behavior (e.g., Dube and McIlvane 1999;Koegel and Wilhelm 1973;Lovaas et al 1971). An alternative view is suggested by the comparator theory of stimulus over-selectivity, which suggests that a comparator mechanism is responsible for selecting between stimuli that potentially could be responded to, and triggers responses only to the most important stimuli available (see Reed 2011).…”
mentioning
confidence: 99%
“…Children with autism are also often attributed with obsessive attentional focus on specific stimuli in their environments. It has therefore been suggested that individuals with autism select only a small subset of the total stimulus array upon which to base newly acquired responding (Lovaas, Schreibman, Koegel, & Rhem, 1971). As a result, transfer to new environments is limited because those incidental stimuli upon which responding is based may not be present in the transfer situation.…”
Section: Introductionmentioning
confidence: 99%